Positive and negative roles of lipids in mast cells and allergic responses. (October 2021) - Kitaura, Jiro; Murakami, Makoto
Highlights: Mast cell-derived cysLTs and PGD2 are potent regulators of type 2 immunity. Microenvironmental PGE2 suppresses mast cell activation and allergic responses. ω3 epoxides derived from EPA and DHA ensure optimal activation of mast cells. The inhibitory CD300-lipid axis acts as a braking system in mast cell activation. Abstract : Mast cells are a central immune cell population that are crucial in allergic responses. They secrete granule contents and cytokines and produce a panel of lipid mediators in response to FcεRI-dependent or independent stimuli. Leukotrienes and prostaglandins derived from ω6 arachidonic acid, or specialized pro-resolving lipid mediators derived from ω3 eicosapentaenoic and docosahexaenoic acids, exert pleiotropic effects on various cells in the tissue microenvironment, thereby positively or negatively regulating allergic responses. Mast cells also express the inhibitory receptors CD300a and CD300f, which recognize structural lipids. CD300a or CD300f binding to externalized phosphatidylserine or extracellular ceramides, respectively, inhibits FcεRI-mediated mast cell activation. The inhibitory CD300-lipid axis downregulates IgE-driven, mast cell-dependent type I hypersensitivity through different mechanisms. Herein, we provide an overview of our current understanding of the biological roles of lipids in mast cell-dependent allergic responses.